A critical re-appraisal of vernacularisation in the emergence and conceptualisation of community bylaws on child marriage and other harmful practices in rural Malawi - Kachika, Tinyade (University of Cape Town, 2020)
The thesis addresses the question: how have international human rights norms for protecting women and girls from harmful practices influenced and shaped the emergence and conceptualisation of community bylaws for addressing child marriage and other harmful practices affecting women in rural Malawi? 'Community bylaws' is a label for Chief-led community 'rules' aimed at combating harmful practices, which mostly affect women and girls. This thesis contributes to the theoretical discourse on norm diffusion by critically assessing and appraising the way in which scholars have conceptualised how international human rights norms are internalised, and, particularly, how vernacularisation operates, through a case study of the community bylaws. Drawing from qualitative empirical data following a study conducted in four districts covering the three regions of Malawi, the study focused on the territories of four Senior Chiefs. Data was gathered through semi-structured interviews with Senior Chiefs and government officials, NGOs, and donors; and through focus group discussions with Group Village Heads, Village Heads, groups that formulated or monitor the implementation of community bylaws, and women living under these bylaws. The thesis shows that while scholars have sought to explain how international human rights norms are appropriated in local communities using the concept of vernacularisation, existing conceptualisations do not adequately represent what is happening with the community bylaws phenomenon. Vernacularisation is a unicameral concept that sees human rights ideas and programmes as being purposefully introduced in local communities by epistemic outsiders. Based on empirical data, this thesis argues that the concept of 'horizontal vernacularisation' better describes the processes occurring in respect of community bylaws in Malawi. This concept has regard to vernacularisation as a bicameral act, whereby the local can also trigger vernacularisation, whether knowingly or not. Thus, horizontal vernacularisation acknowledges that human rights appropriation and translation through community bylaws unfolds within a predominantly local-local dialogue, and is not usually structured, since the bylaws sprout in a continuum of intuitive, interlocking, convoluted, and iterative processes. As such, this thesis contributes to a deeper understanding of community bylaws in rural and cultural settings, and their role in reconceptualising the internalisation of international human rights norms for protecting women and girls from harmful practices.